(untitled) (Journal of Fiber Bioengineering and Informatics, 2019)
The stiffness of the elastic fin for underwater propulsion may need to change concerning its bending speed. In order to realize the bending speed dependence of stiffness in relation to the structure, we have developed an anisotropic viscoelastic fin containing fiber composite dilatant fluid. For the bending test of the fin to examine its stiffness, the top of the fin is fixed, while the base of the fin is rotated. The bending resistance force, as the apparent stiffness of the fin, was measured by the load cell connected to the top of the fin. Bending resistance of the fin containing dilatant fluid increased as the average angular velocity of bending increased. Furthermore, bending resistance of the fin increased according to the existence of fiber, especially the fin along the longitudinal direction of the fiber. This developed fin is a highly functional structure, which can adapt to the demands of changing optimum stiffness with regard to different directions of deformation speed.